Strategic Innovation and Performance of State-Owned Sugar Processing Firms in Nyanza Region, Kenya - Chacha , Joseph Monanka; Juma, Dennis (Journal of Business and Strategic Management, 2025)
Purpose: The general objective of this study was to examine the influence of strategic innovation on the performance of state-owned sugar processing companies in Nyanza, Kenya. Specifically, the study aimed to investigate the impact of the innovative processes, technological innovation and innovative product development and market innovation against the performance of state-owned sugar factories in the Nyanza region. Methodology: The study used a descriptive approach. The target population was 300 respondents, and the researcher used the Yamane formula to arrive at the best sample size of 171 respondents. Data was collected using structured questionnaires. Collected data was cleaned, sorted and coded in ordinal scale using numerical numbers and entered in SPSS software version 29 and presented in form of tables and figures. Findings: The study revealed that the current innovation strategies adopted by the manufacturing firms under study were impactful with 96% of the respondents indicating from moderately to very high impact. The regression analysis confirms that strategic innovation significantly enhances the performance of state-owned sugar firms. Technological innovation (β = 0.412, p = 0.001) had the strongest impact, followed by innovative processes (β = 0.381, p = 0.004), showing that firms that modernize operations and optimize workflows achieve better efficiency and cost reductions. Innovative product development (β = 0.298, p = 0.015) and market innovation (β = 0.275, p = 0.022) also contribute positively, emphasizing the need for continuous product differentiation and adaptive marketing strategies. Unique Contribution to Theory, Policy and Practice: Strategic innovation is critical for improving efficiency, competitiveness, and sustainability in state-owned sugar firms. Technological advancements and process optimization have the greatest impact, while product and market innovation enhance differentiation and customer engagement. Firms must integrate all four dimensions to maximize performance gains. Firms should invest in modern technology, automation, and data-driven decision-making, enhance process efficiency, diversify product offerings, and adopt digital marketing strategies. Government support, policy reforms, and industry partnerships are key to ensuring long-term sustainability and competitiveness.